Bicarbonate-enhanced transformation of phenol upon irradiation of hematite, nitrate, and nitrite - Serge, Chiron; Stephane, Barbati; Swapan, Khanra; Binay K., Dutta; Marco, Minella; Claudio, Minero; Valter, Maurino; Ezio, Pelizzetti; Davide, Vione (ROYAL SOC CHEMISTRY, THOMAS GRAHAM HOUSE, SCIENCE PARK, MILTON RD, CAMBRIDGE CB4 0WF, CAMBS, ENGLAND, 2009)
Bicarbonate enhances the transformation of phenol upon irradiation of hematite, and phenol nitration upon irradiation of both nitrate and nitrite. Hematite under irradiation is able to oxidise the carbonate ion to the CO3-center dot radical, which in turn oxidises phenol to the phenoxyl radical faster compared to the direct photo-oxidation of phenol by hematite. The formation of CO3-center dot from hematite and carbonate under irradiation is supported by the detection of 3,3'-dityrosine from tyrosine, added as a probe for CO3-center dot . It is shown that Fe(III) might be an important photochemical source of CO3-center dot in Fe-rich waters, e. g. waters that contain more than 1 mg L-1 Fe. The enhancement by bicarbonate of phenol nitration upon nitrate irradiation is probably accounted for by an increased photogeneration rate of nitrogen dioxide. The process could lead to enhanced phenol photonitration by nitrate in waters rich of inorganic carbon (> 10 mM bicarbonate). Bicarbonate also increases the transformation and nitration rates of phenol upon nitrite photolysis. The effect is due to the combination of basification that enhances phenol nitrosation and nitration, and of peculiar bicarbonate chemistry. It is shown that bicarbonate-enhanced phenol nitration upon nitrite photolysis could be a significant photonitration pathway, leading to the generation of toxic nitrated compounds in natural waters in which the scavenging of hydroxyl radicals by nitrite is competitive with that of Dissolved Organic Matter (DOM).